2004
DOI: 10.2105/ajph.94.9.1567
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Physical Activity, and the Risk of Decline in Overall Health and Physical Functioning in Late Middle Age

Abstract: Maintaining ideal body weight is important in preventing decline in overall health and physical functioning. However, regular exercise can reduce the risk of health decline even among individuals who cannot achieve ideal weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(84 citation statements)
references
References 33 publications
4
77
1
2
Order By: Relevance
“…In addition, the construct validity and the predictive validity of the LTPA questions appear good: we have previously reported that people who are overweight and obese performed less LTPA, and individuals who performed more LTPA were less likely to have a decline in overall health and physical functioning. 12 The validity of self-reported WRPA is less clear, and this is an important area for future research. The lack of an association between WRPA and health outcomes may be due to imprecise measurement of WRPA or from some physiologic difference between WRPA and LTPA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the construct validity and the predictive validity of the LTPA questions appear good: we have previously reported that people who are overweight and obese performed less LTPA, and individuals who performed more LTPA were less likely to have a decline in overall health and physical functioning. 12 The validity of self-reported WRPA is less clear, and this is an important area for future research. The lack of an association between WRPA and health outcomes may be due to imprecise measurement of WRPA or from some physiologic difference between WRPA and LTPA.…”
Section: Discussionmentioning
confidence: 99%
“…Population studies have shown that LTPA is a predictor of coronary heart disease, [29][30][31][32][33][34][35][36] overall health, and physical functioning. 12 However, it has not been clearly shown that higher levels of WRPA lead to better health. 10,37,38 Thus, lower levels of LTPA among the less educated help explain socioeconomic disparities in health, as well as health disparities for blacks and Latinos as a result of the lower educational attainment among these groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult obesity has been associated with a higher prevalence of musculoskeletal disorders, primarily affecting the lower limbs, [9][10][11][12][13] but comparative data in children are scarce. Some musculoskeletal disorders that are unique to childhood, such as slipped capital femoral epiphysis 14 and tibia vara (Blount's disease), 15 [16][17][18][19] Although these few studies imply that childhood obesity may predispose children to musculoskeletal problems, convincing empirical verifi cation is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the encouraging results on the potential that physical activity has in ameliorating functional limitations or postponing them to later life on the population level, the results for obese persons are inconsistent [54][55][56][57][58]. Brach et al showed with data from a 14-year follow-up to a walking intervention trial that consistent physical activity compensated for the detrimental influence of obesity among older community-dwelling women.…”
Section: The Progression Of Functional Limitations and Physical Activmentioning
confidence: 99%